MODERN MILITARY-TACTICAL INTEGRATION OF LOCAL PHYTOCHEMICAL RESOURCES: NANOTECHNOLOGICAL MODIFICATION AND THE PROSPECTS OF AUTONOMOUS PRECISION SYSTEMS (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article investigates the historical application, chemical-biological characteristics, and advanced technological and nanotechnological prospects of active alkaloids within local agro-industrial raw materials - hot pepper (Capsicum) - in the military and law enforcement spheres, as well as their deployment in the contemporary Multi-Domain Operations theater. The mechanisms through which capsaicin, the active chemical agent in pepper, impacts human neuro-receptors and cognitive stability are analyzed from a biological perspective. Furthermore, the paper provides a scientific substantiation for the strategic-tactical prospects of extracting the Oleoresin Capsicum (OC) phytochemical agent from local cultivars such as Margilan-333, microencapsulating it, and integrating it into drone ecosystems within the defense industry framework of the Republic of Uzbekistan under conditions of global logistical crises.
Keywords: Phytochemical defense, Capsicum, microencapsulation, nano-carriers, UAV tactics, cyber-physical barriers, green defense, Oleoresin Capsicum, TRPV1 modulation, non-lethal weapons, cognitive dispersion.